Roles of extracellular vesicles from different origins in metabolic-associated fatty liver disease: progress and perspectives - Wang, Jing; Bao, Shuoqiang; An, Qi; Li, Caihong; Feng, Juan (Frontiers in Immunology, 2025)
Metabolic-Associated Fatty Liver Disease (MAFLD) is the most common chronic liver disease worldwide, associated with systemic metabolic dysregulation. It can progress from simple hepatic steatosis (MAFL) to more severe conditions like Metabolic-Associated Steatohepatitis (MASH), fibrosis, cirrhosis, and Hepatocellular Carcinoma (HCC). There is a critical lack of reliable non-invasive diagnostic methods and effective pharmaceutical treatments for MAFLD/MASH, emphasizing the need for further research. Extracellular vesicles (EVs) are nanoscale structures that play important roles in cell signaling by delivering bioactive molecules. However, there is a significant gap in literature regarding the roles of EVs from hosts, plants, and microbiota in MAFLD. This review explores the potential of EVs from various sources—host, plants, and microbiota—as biomarkers, therapeutic agents, drug carriers, and treatment targets for MAFLD. Firstly, the roles of host-derived extracellular vesicles (EVs) in MAFLD, with a focus on cell-type specific EVs and their components—proteins, miRNAs, and lipids—for disease diagnosis and monitoring were discussed. Moreover, it highlighted the therapeutic potential of mesenchymal stem cell (MSC)-derived EVs in reducing lipid accumulation and liver injury, and immune cell-derived EVs in mitigating inflammation and fibrosis. The review also discussed the use of host-derived EVs as drug carriers and therapeutic targets due to their ability to deliver bioactive molecules that impact disease mechanisms. Additionally, it summarized research on plant-derived EVs, which help reduce liver lipid accumulation, inflammation, and enhance gut barrier function in MAFLD. Also, the review explored microbial-derived EVs as novel therapeutic targets, particularly in relation to insulin resistance, liver inflammation, and dysfunction in MAFLD. Overall, by exploring the diverse roles of EVs from host, plant, and microbiota sources in MAFLD, this review offers valuable insights into their potential as non-invasive biomarkers and novel therapeutic strategies, which could pave the way for more effective diagnostic and treatment options for this increasingly prevalent liver disease. Notably, the challenges of translating EVs into clinical practice were also thoroughly discussed, aiming to provide possible directions and strategies for future research.